Strategi public relations bank syariah indonesia dalam membangun hubungan dengan generasi z - Mukti, Fitri Ana (Maliki Interdisciplinary Journal, 2025)
Generation Z is a demographic group raised in the digital era, characterized by adaptability, critical thinking, and strong reliance on technology. In Islamic banking, Generation Z represents a vital segment for sustainable growth. This study aims to analyze the Public Relations (PR) strategies of Bank Syariah Indonesia (BSI) in building relationships with Generation Z. The research applies a qualitative descriptive method through literature review and observation of BSI’s digital media content. The findings reveal that BSI develops digital-based PR strategies through social media engagement, influencer collaboration, and interactive communication emphasizing Islamic values and message authenticity. These strategies strengthen BSI’s positive image and build Generation Z’s trust and emotional connection with Islamic banking. In conclusion, effective PR strategies for BSI emphasize transparent, interactive communication aligned with sharia principles.